Experimental study of the production of resin granite and marble using their solid waste - Santos, Vinicius Rodrigues Dos; Genova, Luís Mateus [UNESP]; Soares, Silvete Mari; Cabral, Thiago Baltor; Lovo, João Fiore Parreira; Carmo, Devaney Ribeiro Do [UNESP] (FapUNIFESP (SciELO), 2024)
Structural materials play an essential role in equipment and constructions, with properties such as strength and stability. Granite and marble are widely used for structural building materials such as cladding, sinks and countertops. It is possible to recycle waste from these rocks in the production of new parts, reducing the environmental impact. In Brazil, there is a high amount of construction and demolition waste, with most of the raw material becoming waste before the product is finished. Studies indicate that the incorporation of ornamental stone waste into cementitious products can significantly reduce environmental impact and improve its sustainability. The present work presents an experimental study for the manufacture of resin granite test specimens with residues from different dosages and resin epoxy levels. Flexural strengths of up to 7, 11, 24 and 28 MPa are achieved for resin contents of 5%, 10%, 15% and 20% respectively. The material has anisotropic characteristics and makes good use of almost all of the size ranges of waste used. Future reverse engineering studies of the resin are also necessary to expand knowledge and further optimize its application.
Keywords: construction; demolition waste; marble; recycled granite; Resin granite; synthetic granite